Eating disorders in under 5 years old and their relationship with family functionality: Trastornos alimentarios en menores de 5 años y su relación con la funcionalidad familiar - García-Galicia, Arturo (2021)
Introduction: Eating disorders under 5 years old may cause development and grow problems. Disorders in family functionality can be associated. Objective: To describe non-organic eating disorders in children under 5 years of age and their association with family functionality in a second-level hospital in Puebla. Methods: It was a descriptive, cross-sectional study. Children under 5 years old with non-organic eating disorders were included. A questionnaire to study eating disorders (IMFED) and other one to describe family functionality (FACES III) were applied to their parents who previously signed informed consent. Descriptive statistics and Spearman test were used. Results: 105 patients were evaluated, 57 men and 48 women, medium age 3.042, minimum 2, maximum 60, ± 16.68 months old. Children 12-23 months old were more frequent. Parents reported chaotic family adaptability in 45.71%, and 39.04% related cohesion. The most frequent eating disorder was sensorial aversions to food. More than 60% had two or more eating disorders. Family adaptability and eating disorders were correlated in 0.248(p=0.011), and family cohesion and eating disorders 0.87 (p=0.38). Conclusion: Most frequent eating disorders were sensorial aversion to food and infant anorexia. They softly correlate with family adaptability. Children under 5 years old with 2 or more eating disorders are more frequent.